RETRACTED: Oncological Effects and Prognostic Value of AMAP1 in Gastric Cancer - Li, Jiao; Tian, Shan; Guo, Yingyun; Dong, Weiguo (Frontiers in Genetics, 2021)
Purpose We examined the diagnostic significance, prognostic value, and potential function of AMAP1 in gastric cancer (GC). Methods Comprehensive bioinformatic analysis was conducted to investigate differential expression of AMAP1 mRNA and protein in GC. Meta-analyses were utilized to determine the overall prognostic correlation of AMAP1 mRNA in patients with GC. A panel of vitro assays was applied to assess target microRNA and AMAP1 protein in GC cell lines and tissues, respectively. Results AMAP1 mRNA and protein levels were upregulated in GC specimens, compared to matched normal tissues. AMAP1 mRNA exhibited promising results regarding differential diagnosis of GC and normal tissue. Meta-analysis based on the TCGA and GEO databases revealed that high AMAP1 mRNA abundance was associated with poor overall survival (HR = 1.42; 95% CI: 1.06–1.89) and was correlated with reduced progression-free survival (HR = 1.89; 95% CI: 1.51–2.36) in GC patients. Moreover, AMAP1 was negatively correlated with miR-192-3p (r = −0.3843; P < 0.0001). A dual-luciferase assay revealed that miR-192-3p targeted AMAP1. Levels of miR-192-3p were significantly higher in GC tissues and GC cells than in normal tissues and cells. Moreover, AMAP1 silencing resulted in reduced GC proliferation, migration, and invasion. Conclusion AMAP1 is a novel oncogene in GC and is negatively correlated with by miR-192-3p. AMAP1 may act as a diagnostic and prognostic marker of GC.